(untitled) (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2017)
The paper examines innovative and promising trends in in the design of high-rise buildings that challenge traditional typologies and are adapted for specific climatic conditions. The purpose of the study is to investigate modern methods of designing building envelopes for bioclimatic skyscrapers taking into account heat impact of climate on the thermal balance of buildings. The research methodology is based on a systematic analysis of advanced world experience in constructing innovative buildings, "conquering" climate. The paper provides the basic principles of bioclimatic architecture. The issues of buildings’ forms and modes are considered. The authors analyze the efficiency of using double facades in different climatic conditions with account of their interaction with other technological, constructive and planning elements, such as "solar chimney", passive and active solar control systems, landscaping, intelligence control systems of temperature and humidity conditions in premises and buildings, etc. The paper highlights that unique objects of bioclimatic skyscrapers are moving now into new typologies of buildings and help form dense, comfortable and convenient urban environment using natural resources effectively. The research shows how prospects and relevance of a systemic approach to introducing the related and interdependent projects for energy saving activities at all levels, starting from town-planning and architectural models, and ending with engineering and constructive solutions.